Profitability, Free Cash Flow, and Firm Value - Nyoman Cyntia Riesta Utami; Ida Bagus Putra Astika (E-Jurnal Akuntansi, 2024)
The primary goal of a company is to generate high profits and ensure the welfare of its shareholders by increasing the firm’s value. This study aims to provide empirical evidence on the impact of profitability and free cash flow on the value of a firm. The sample for this study encompasses all companies listed on the Indonesia Stock Exchange that have published complete financial reports from 2017-2022. The selection of the sample for this study was done using non-probability sampling, resulting in a sample size of 373 companies. Multiple linear regression analysis techniques were applied in this study, utilizing the STATA application. The results demonstrated that both profitability and free cash flow have a positive influence on a firm’s value.